Post-harvest physiological deterioration of cassava (Manihot esculenta) - A review - SARAVANAN, RAJU; RAVI, VELUMANI; STEPHEN, ROY; THAJUDHIN, SHERIFF; GEORGE, JAMES (The Indian Journal of Agricultural Sciences, 2016)
Cassava (Manihot esculenta Crantz) is a valued root crop grown throughout the tropics for food, feed and biofuel and industrial uses. Fresh cassava roots have short shelf-life due to an endogenous phenomenon called Post-harvest Physiological Deterioration (PPD). The estimated losses fresh cassava roots due to PPD is nearly 1/3rd of total harvest world-wide. PPD symptom starts within 24 hr after harvest, initially as blue black discolouration in the storage parenchyma which quickly spread to entire root. The roots become unfit for consumption within 2-3 days after the harvest in most cases. Several lines of evidence suggest that the PPD of cassava roots is an enzymatic, endogenous oxidative process. Reactive Oxygen Species (ROS) have been shown to increase very early during PPD and strongly correlated with the symptoms and also evidenced by the active involvement of key ROS enzymes during PPD. Increase of phenolic compounds in freshly harvested roots (e.g. scopoletin), accumulation of H